Single Center Characterization of a Cohort of Salivary Gland Carcinomas - Ria Winkelmann; Maja Weißgerber; Peter J. Wild; Julia Bein; Maximilian Fleischmann; Melanie Demes; Panagiotis Balermpas; Andreas Loth; Katrin Bankov; Jens von der Grün (Life)
Salivary gland cancer (SGC) is a rare cancer that can present a diagnostic challenge to pathologists, with emerging, but still limited options for the treatment of recurrent/metastatic disease. We aimed to characterize the cohort of salivary gland cancers in our institute and generate a tissue microarray (TMA) with clinical data available for immunohistochemical analysis. We extracted the cases of salivary gland cancers in our institute and generated a TMA with 72 patients between 2002 and 2017 with sufficient paraffin block material. Follow-up data were present for all cases. The TMA was stained with three p53 antibodies as well as MSH2, MSH6, PMS2 and MLH1 antibodies. Additionally, we applied fragment analysis based on the Bethesda panel, and the IdyllaTM MSI test to cases with expression loss of any of the mismatch repair proteins (MMR-P) according to our immunohistochemistry (IHC). The investigated cohort shows that pT and pN stage are the only factors independently associated with survival, according to our multivariate analysis (p = 0.037 and p = 0.014). In univariate analysis, risk factors identified in our cohort were also age (p = 0.015), (lympho-) vascular invasion (p = 0.002 and p = 0.003) and risk stratification (p = 0.037). The p53 protein investigated by three antibodies showed no statistically significant association with survival or other tumor characteristics in the investigated cohort. According to MMR-P IHC, six cases of SGC showed an aberrant IHC phenotype. Additional IdyllaTM MSI test and fragment length analysis failed to confirm microsatellite instability. The pT and pN stage are the most important factors for survival in our cohort. In our cohort, antibodies directed against the protein p53 did not contribute to clinical decision-making and were not correlated with any known clinical characteristics. MSI appears to be insignificant in SGCs. Larger cohorts are needed for verification.